2001
DOI: 10.1152/ajpheart.2001.281.5.h1919
|View full text |Cite
|
Sign up to set email alerts
|

Chronic decentralization of the heart differentially remodels canine intrinsic cardiac neuron muscarinic receptors

Abstract: The objective of the study was to determine if chronic interruption of all extrinsic nerve inputs to the heart alters cholinergic-mediated responses within the intrinsic cardiac nervous system (ICN). Extracardiac nerve inputs to the ICN were surgically interrupted (ICN decentralized). Three weeks later, the intrinsic cardiac right atrial ganglionated plexus (RAGP) was removed and intrinsic cardiac neuronal responses were evaluated electrophysiologically. Cholinergic receptor abundance was evaluated using autor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Muscarinic agonists exert major neuromodulating effects on IC neurons, and these effects can be altered in pathophysiological states (Bibevski and Dunlap, 2011; Dunlap et al, 2003; Smith et al, 2001). Bethanechol increased neuronal excitability over baseline levels following MI (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Muscarinic agonists exert major neuromodulating effects on IC neurons, and these effects can be altered in pathophysiological states (Bibevski and Dunlap, 2011; Dunlap et al, 2003; Smith et al, 2001). Bethanechol increased neuronal excitability over baseline levels following MI (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Labeling of ␤ 1-and ␤2-ARs in 20-m thick sections of unfixed LV myocardium was done by a modification of published protocols (14,20) using l-[ 125 I]iodocyanopindolol (PerkinElmer Life Sciences; Boston, MA), which is a membrane permeant ligand and measures both extracellular and intracellular receptors. Total binding was determined by incubation of sections for 90 min at 37°C in a Tris-salt buffer containing 0.1 nM [ 125 I]cyanopindolol, 10 M pargyline, and 10 M serotonin.…”
Section: Receptor Autoradiographymentioning
confidence: 99%
“…Incubation buffers for other sections also contained 3 M timolol (nonspecific binding) or 0.5 M CGP-20712A, a ␤ 1-AR antagonist. Radioligand binding sites were identified by film autoradiography and quantified by using a microcomputer-assisted imaging device (Imaging Research) as described previously (20). Total ␤-AR levels were calculated by subtracting nonspecific binding from total binding.…”
Section: Receptor Autoradiographymentioning
confidence: 99%
“…It is well demonstrated that increasing age drastically changes autonomic tone, perhaps in part due to the loss of autonomic neurons, reduced responsiveness to autonomic stimuli or a combination of the two. Smith et al demonstrated that even weeks after denervation of the ECNS, GP neurons remain fully viable and retain their ability to increase neurotransmitter release 48 . Thus, it is conceivable that as a person ages there may be an increased proclivity for AF owing to autonomously functioning GPs in the absence of strong autonomic tone.…”
Section: Large Animal Studiesmentioning
confidence: 99%